DEMAM DENGGI DI TEMERLOH - SATU ANALISIS DI LOKALITI UTAMA WABAK - Abu Bakar AN; Suzana MH (Malaysian Journal of Public Health Medicine, 2004)
The aim of this study was to describe the sociodemographic aspect, clinical presentation and laboratory support, behaviour factor and vector situation of dengue outbreak. Data was obtained from standard investigation format of 84 cases of suspected dengue fever in two main outbreaks localities in Temerloh District from December 2001 to January 2002. The result showed that most of the cases occured among 11 years old and above, especially in the age group of 11 to 20 years old. Students and females were the most high-risk groups. Rashes and petechiae were more prevalent in Taman Sri Semantan which reflect the case incidence there. Serological result showed that seroprevalence for lgM was 66 .1 % . Based on dengue rapid test, secondary infection was more prevalent in Taman Sri Kemuning whereas those in Taman Sri Semantan had more primary infection. About 25% of the cases came late to hospital for treatment. Both localities had different mosquito breeding areas. Further studies are needed to identify behaviour aspect of the population with regard to dengue fever in previous main outbreak localities. A more valid and rapid serological test is required for better case identification.